EFFECTIVENESS OF INTERACTIVE LEARNING MEDIA WITH CANVA APPLICATION IN AN EFFORT TO IMPROVEREADING ABILITY ARABIC TEXTS AT TADIKA AL-FIKH ORCHAD - Tanjung, Ellisa Fitri; Nurzannah, Nurzannah; Akrim, Akrim (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
In accordance with the development of a new paradigm in learning, as a result of developments in science and technology, especially information and communication technology, of course the skills that must be possessed can develop according to current demands. Learning media are the means or tools used by (teachers) to convey lesson material to students so that the learning process can achieve the desired goals, be effective, efficient and attractive. Learning media is very important in the learning process because teachers can convey material to students in a more meaningful way. Teachers do not only deliver material in the form of words with lectures but can bring students to truly understand the material presented. This research aims to describe how teachers at Tadika Al- Fikh Orchid Malaysia use Islamic religious education learning media. Method used is method descriptive, with approach study qualitative. Type of research This is study field (field research). Research focuses on collecting descriptive data, observations, interviews, or analysis in-depth text, with objective For understand context, meaning, and experience subject. Observation done to activities that include development of image media and canva, such as word cards, reading media spell based on application, big book media, learning media read through game word board, image media based on analysis structural synthetic, and development of learning media use Speech To Text. Research This carried out at the Tadika Al-Fikh Orchad Malaysia school. As for targets study are teachers of Islamic religious education